The Effective Level of Intensive English Program on English Speaking Proficiency in First Year University Students - Sasmita Tarihoran; Jufrizal Jufrizal (Indonesian Journal of Foreign Language Studies, 2026)
This study examined the level of effectiveness of intensive English program on the speaking skill of students at the Islamic University of Syekh Ali Hasan Ahmad Ad-Dary (UIN SYAHADA) Padangsidimpuan during the 2023/2024 academic year. It specifically targeted first-semester English major students, with the primary aim of this research is to investigate how effectively the program fostered their English-speaking abilities. The researcher used descriptive research involved collecting data from 43 students through a validated and reliable questionnaire designed based on Slavin's indicators which include the quality of learning, appropriate instruction level, motivation, and time management. The results revealed that while the program excelled in several important areas, including the quality of learning materials and the effectiveness of teaching methods, there was notable room for improvement in other aspects. Specifically, the program needed to better ensure students' physical and emotional readiness for learning and more effectively manage the allocation of time for various learning tasks. The findings from this research offered valuable insights for policymakers and educators, guiding them in making informed decisions to enhance the overall effectiveness of the language program. By addressing these identified challenges, the program could be better tailored to support students in overcoming obstacles and achieving greater proficiency in their English-speaking skills, ultimately contributing to their academic success and personal development.